Termitaphididae, a family of true bugs (Heteroptera) new to Brazil, with the redescription of Termitaradus trinidadensis - Carvalho-Filho, Fernando Da Silva; Fernandes, José Antônio Marin (Zootaxa, 2020)
The family Termitaphididae and the species Termitaradus trinidadensis (Morrison) are recorded for the first time from Brazil. This species had been found only in Trinidad and Tobago and is redescribed based on specimens collected in Heterotermes tenuis (Hagen) termite nests from forested and open areas in the Brazilian Amazon. Scanning electron micrographs of integumental ornamentation, illustrations of male and female terminalia, and pictures of live specimens are provided for the first time.